Digital Supply Chain Mechanism in Indonesian Society and Industrialization - Suparto Wijoyo; Bagus Oktafian Abrianto; M. Syaiful Aris; Xavier Nugraha; Ave Maria Frisa K (International Journal of Supply Chain Management, 2020)
Abstract— The electronics industry has been a key driver of economic growth and employment in many developing countries, including Indonesia. Participating in global electronics supply chains can have several benefits, including the growth of domestic industries as competitors and suppliers, and increasing exports. This study uses a normative legal research method with the statutory approach, conceptual approach, and case approach. Based on the digital supply chain in Indonesian society and industry for implementing DSCM in Indonesia, namely, First, it does not violate the principle of direct, general, free, confidential, honest, and fair. Second, the regions that apply the DSCM method are ready in terms of technology, financing, human resources and software, the readiness of the people in the area concerned, as well as other requirements needed